2011
DOI: 10.1088/0957-0233/22/4/045101
|View full text |Cite
|
Sign up to set email alerts
|

Troposphere modeling for precise GPS rapid static positioning in mountainous areas

Abstract: In global navigation satellite system precise positioning, double differencing of the observations is the common approach that allows for significant reduction of correlated atmospheric effects. However, with growing distance between the receivers, tropospheric errors decorrelate causing large residual errors affecting the carrier phase ambiguity resolution and positioning quality. This is especially true in the case of height differences between the receivers. In addition, the accuracy achieved by using stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 16 publications
(17 reference statements)
0
18
0
Order By: Relevance
“…Satirapod and Chalermwattanachai (2005) and Wielgosz et al (2011) may be cited. Some of the publications where the authors have researched the behaviour of tropospheric residuals are Musa (2007) and Ibrahim and El-Rabbany (2007).…”
Section: Tropospheric Refractionmentioning
confidence: 99%
“…Satirapod and Chalermwattanachai (2005) and Wielgosz et al (2011) may be cited. Some of the publications where the authors have researched the behaviour of tropospheric residuals are Musa (2007) and Ibrahim and El-Rabbany (2007).…”
Section: Tropospheric Refractionmentioning
confidence: 99%
“…The positioning using the above methods can be supported by Ground Base Augmentation System (GBAS), which provides better results stability in the area of the GBAS network (Kee et al, 1991). One of the elements supporting precise positioning, especially for height component, is a model of the neutral atmosphere (troposphere), computed for the GBAS network area (Wielgosz et al, 2011;Grejner-Brzezinska et al, 2009). The Poland territory is covered by dense network of GNSS stations in the frame of a GBAS system called ASG-EUPOS.…”
Section: Introductionmentioning
confidence: 99%
“…As our previous research has shown for precise positioning with very short sessions, it is not recommended to estimate zenith tropospheric delay (ZTD) in the rover solution due to the slight change in satellite geometry (Wielgosz et al 2011a). For reliable estimation of ZTD, a significant distance between the stations is required (Dach et al 2007;Wielgosz et al 2011b).…”
Section: Methodsologymentioning
confidence: 99%